Desenvolvimento de biocompósito à base de amido adicionado de tio2 e argila para aplicação em célula fotovoltaica - Boane, Jenny Luis Nhaliguangue (2015)
Starch-based biocomposites, being biodegradable, have been studied in various fields for many purposes, with emphasis in the food industry. The addition of plasticisers, titanium oxide (TiO2) particles and montmorillonite (MMT) clay improve the thermal and physical properties of biocomposites. This study was conducted with the objective of developing, preparing and characterizing biocomposites (starch + glycerin + montmorillonite (MMT) + TiO2 with different particle size (0.5 µm; 250 nm and < 100 nm); assessing the efficiency of the biocomposites obtained. We prepared seven mixtures: by means of the solvent evaporation technique (casting): 1 – starch biocomposite + glycerol, 2 - starch biocomposite + TiO2 0.5 µm, 3 - starch biocomposite + TiO2 250 nm, 4 - starch biocomposite + TiO2 < 100 nm, 5 - starch + MMT + TiO2 0.5 µm, 6 – starch biocomposite + MMT + TiO2 250 nm, 7 – starch biocomposite + MMT + TiO2 < 100 nm. The samples were characterized by thermal (DSC and TGA), morphological (SEM), physical-chemical (diffuse reflectance (Gap), FT-IR) and energy (strength, resistivity and efficiency) analyses. In the samples containing TiO2, we did not observe homogeneity or good dispersion of the TiO2 particles in the mixture. This result is due to the incompatibility of the TiO2 particles with starch, on the other hand, there is good intercalation of MMT in the starch matrix, related to the hydroxyl group and the amino group present in the starch. We concluded that the mixtures made with the purpose of application in solar cells were not efficient in virtue of incompatibility of the composites with the starch matrix, therefore suggesting its application in other technological areas.